Evaluation of WiFi Broadband Network on the Jabodetabek Commuter Line - Eka Sartika Rosiana; Karijadi Karijadi; Makhdor Rosadi; Rivira Yuana; Taswanda Taryo; Lilly S Wasitova; Abdul Multi; Lukman Medriavin Silalahi (International Journal of Engineering Continuity, 2026)
This research evaluates the performance of WiFi networks based on the Universal Mobile Telecommunications System (UMTS) backbone on the Commuter Line (CL) to identify technical issues in providing stable internet services in public transportation with high mobility. The main gap lies in the inability of the existing infrastructure to maintain service continuity when the train is mobile compared to when it is immobile. This research uses an experimental method involving three testing scenarios (using a backbone modem, a signal measurement system, and a smartphone device); the study measures Quality of Service (QoS) parameters. Research results show that throughput passing through the UMTS backbone decreased by 16.8% to the DNS server and 12.68% to detik.com when the commuter line was in motion. Furthermore, packet loss passing through the UMTS backbone increased by 13.6% to the DNS server and 11.2% to detik.com when the commuter line was moving. Then, the round trip time passing through the UMTS backbone increased by 175.50% to the DNS server and 179.25% to detik.com when the commuter line was in motion. These results confirm that high mobility causes significant signal degradation, making current UMTS networks not yet capable of supporting users' broadband needs inside train carriages. The contribution of this research is is recommending a new infrastructure design in the form of optimizing BTS placement or using train repeaters to address interference. Therefore, the conclusion of this research is the need to strengthen transmission in the CL so that the WiFi implementation can achieve the expected reliability standards.